Structures of human salivary amylase hydrolysates from starch processed at two water concentrations. Issue 7 (30th January 2013) - Nantanga, Komeine K. M.; Bertoft, Eric; Seetharaman, Koushik
Abstract Digestion of starch in humans starts in the mouth and progresses to the small intestine. A thorough understanding of the progression of digestion, of consequence to glycemic and possibly insulinemic responses, requires a better characterization of the digestion products along the gut – products that are the substrates in the subsequent hydrolysis by sucrase‐isomaltase and maltase‐glucoamylase. This submission focuses on the first step of digestion, i.e., impact of human salivary amylase on the structure of hydrolysis products obtained from cooked starch. Starch was cooked at 1:0.7 (T0.7) or 1:2 (T2) starch:water ratios. To remove the effect of granular structure, starch was also dispersed using DMSO (TD) prior to amylase treatment. Cooked and dispersed starches were subjected to salivary amylase at conditions mimicking oral digestion. All samples gave rise to different and complex mixtures of hydrolysates with broad size‐distributions as measured by gel‐permeation chromatography (GPC). Following hydrolysis, the smallest dextrins (DP <30) constituted 35% in TD and only ∼20% in both T0.7 and T2. Cooking appeared to protect amylose molecules from hydrolysis with less hydrolysis in T0.7. These results show that the amount of water present during processing of starch affects structures of salivary amylase hydrolysates, which potentially impact on glucose homeostasis.